2020
DOI: 10.1101/2020.01.28.923177
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An empirical attack tolerance test alters the structure and species richness of plant-pollinator networks

Abstract: Ecological network theory hypothesizes a link between structure and stability, but this has mainly been investigated in-silico. In an experimental manipulation, we sequentially removed four generalist plants from real plant-pollinator networks and explored the effects on, and drivers of, species and interaction extinctions, network structure and interaction rewiring. Our results indicate that cumulative species and interaction extinctions increased faster with generalist plant loss than what was expected by co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 63 publications
2
30
0
Order By: Relevance
“…The changes we observed in pollinator visitation rates and species composition in response to the removal of Helianthella flowers gave rise to the altered structural properties of the plant-pollinator interaction networks. Other experiments that have removed generalist plant species have found conflicting results: Biella et al (2020) observed increased network specialization, whereas others have observed increased generalization (Goldstein and Zych 2016, Kaiser-Bunbury et al 2017). Here, we find that experimental floral removal gave rise to more specialized and less nested networks.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The changes we observed in pollinator visitation rates and species composition in response to the removal of Helianthella flowers gave rise to the altered structural properties of the plant-pollinator interaction networks. Other experiments that have removed generalist plant species have found conflicting results: Biella et al (2020) observed increased network specialization, whereas others have observed increased generalization (Goldstein and Zych 2016, Kaiser-Bunbury et al 2017). Here, we find that experimental floral removal gave rise to more specialized and less nested networks.…”
Section: Discussionmentioning
confidence: 93%
“…To date, relatively few studies have experimentally removed plant or pollinator species from intact pollination networks to investigate the consequences of their loss, but the available evidence suggests a variety of responses (plant removals: Biella et al 2020; Biella et al, 2019; Ferrero et al 2013; Goldstein and Zych 2016; Kaiser-Bunbury et al 2017; pollinator removals: Brosi and Briggs 2013; Brosi et al 2017). Complete removal of generalist floral resources from a landscape can bring about dramatic reductions in visitation rates and redistribution of visitors to the remaining plant community (Biella et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we argue that TCM has also still some interpretative advantages over SCM: the SCM assumes that each species depends on its partners proportionally to the observed frequencies of interactions between them, so it does not take into account the flexibility of species (in our case pollinators) to shift their interactions after the extinction of some of their previous partners (visited plants). Such flexibility has been experimentally documented for example by Biella et al (2019, 2020). On the other hand, TCM assumes the opposite extreme, i.e.…”
Section: Introductionmentioning
confidence: 90%
“…that a species survives until any single partner of the species remains present. Despite their conceptual differences, both coextinction models received comparable empirical support based on field experiments in grasslands in central Europe (Biella et al 2020). Moreover, the simulations can be used to quantify the functional importance of individual species in the network (Pocock et al 2012).…”
Section: Introductionmentioning
confidence: 99%